(untitled) (Itinera, 2015)
The study provides an overview of the well-known controversy about Friedrich Creuzer’s Symbolik und Mythologie der alten Völker, besonders der Griechen, seen from the point of view of classical philology. Particular attention is paid to the position of Gottfried Hermann, and to the role he reserved to language in the study of myth, in the context of the epistemological controversies that dominated the classical studies in Germany during the XIXth century.